Femoral muscle mass relates to physical frailty components in community‐dwelling older people. Issue 10 (26th January 2017) - Takahashi, Tetsuya; Sugie, Masamitsu; Nara, Marina; Koyama, Teruyuki; Obuchi, Shuichi P; Harada, Kazumasa; Kyo, Syunei; Ito, Hideki
Abstract : Aim: To examine the relationship between lower limb muscle (femoral muscle, calf muscle) mass and exercise capacity, and frailty components in community‐dwelling older people. Methods: Participants included 121 community‐dwelling individuals. There were 42 men and 79 women, and the mean age was 77.7 years (range 56–97 years). Appendicular skeletal muscle mass was determined using dual‐energy X‐ray absorptiometry, and the skeletal muscle index was calculated using the following formula: appendicular skeletal muscle / body height 2 . Femoral muscle mass and calf muscle mass were determined, respectively, by dividing the femoral bone and tibial bone at the knee joint space. A symptom‐limited cardiopulmonary exercise testing was carried out and peak oxygen uptake was measured. Functional exercise performance was evaluated using the handgrip strength measurement, comfortable walking speed, and the Timed Up and Go test. All patients gave written, informed consent before data collection. Results: Peak oxygen uptake correlated positively with the skeletal muscle index ( r  = 0.491). Only femoral muscle mass that was corrected with the whole body muscle mass was positively correlated with peak oxygen uptake ( r  = 0.473), handgrip strength ( r  = 0.382), comfortable walking speed ( r  = 0.427), and the Timed Up and Go test ( r  = 0.379). Calf muscle mass that was corrected with the whole‐body muscle mass showed no correlation with exercise capacity and frailty components. A similar tendency was observed in both men and women. Conclusions: Femoral muscle mass influenced exercise capacity and physical frail components compared with calf muscle mass. These results suggest the importance of the femoral muscle in physical frailty.Geriatr Gerontol Int 2017; 17: 1636–1641.